Persepsi Masyarakat tentang Kebijakan Pelayanan Angkutan Laut di Kabupaten Raja Ampat - , Semuel Belseran, S.Sos., Dr. Wahyu Widayat, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The availability of marine transportation infrastructure is one of the crucial factors influencing the economic development of local community both for human passenger and goods with sufficient quantity in interaction among great and small islands between Sorong and Waisai. They are is important because naval ship is a main marine transportation vehicle going to and turning around the Raja Ampat islands to Sorong Port. However, there is to date no study on the integrated policy of marine transportation development in the regency. Therefore, the objectives of the study are to describe general policies of marine transportation service in Raja Ampat Regency